Implementation of Differentiated Learning of Merdeka Curriculum in Catholic Religious Education Lessons - simbolon, Erikson; Bangun, Andry Ella Paustina (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
This research aims to determine how differentiated learning is implemented in Catholic Religious Education subjects at Budi Murni 2 Medan Junior High School. The research method used is qualitative research, which uses data collection techniques through observation, interviews, and documentation. Data analysis techniques are done through data reduction, display, and conclusion drawing. Differentiated learning is motivated by ecological theory, multiple intelligences, zone of proximal development, and learning modalities.  Differentiated learning applied by Catholic Religious Education teachers is implemented through three aspects: content, process, and product differentiation. The results of the study found that Catholic Religious Education teachers have implemented differentiated learning well, but in its implementation, there are obstacles experienced by teachers, including time constraints, variations in students' abilities and learning styles, classroom management, and students' readiness. The implications of this research make students enthusiastic about participating in Catholic Religious Education learning. This enthusiasm is manifested through changes in the active participation of students in learning. The differentiation strategy can also fulfill learners' individual learning needs, increase their involvement and motivation in the learning process, and help them effectively achieve learning objectives.